RESEARCH OF STRUCTURAL AND MECHANICAL PROPERTIES OF MEAT AS AN OBJECT OF PROCESSING IN MEAT COMMINUTOR - ANTONYUK, VIKTOR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article presents the results of a comprehensive analytical study on the influence of various face milling parameters on the machinability of high-hardness steels. The focus is on the use of polycrystalline cubic boron nitride (PCBN) tools, both uncoated and coated, which demonstrate high wear resistance and stability when machining hard-to-machine materials. The analytical studies include the analysis of the effects of cutting parameters, such as cutting speed, depth of cut, and feed rate, as well as cooling and lubrication methods on the quality of the machined surface and the wear resistance of the tools. The use of PCBN tools from different groups with varying geometries significantly improves process productivity and reduces maintenance costs due to their ability to withstand high temperatures and high mechanical loads. The experiment compares the effectiveness of PCBN tools from different groups. It has been shown that PCBN tools provide better surface quality and exhibit less wear under high-speed milling conditions. The study also considers various cooling methods and their impact on the wear resistance of the tools and the quality of the machined surface. Special attention is given to optimizing face milling parameters to achieve maximum process efficiency, particularly reducing surface roughness of high-hardness steels. Recommendations have been developed for selecting optimal cutting regimes that minimize tool wear and improve surface roughness. The article also explores the prospects of introducing new technologies and materials into production, which can significantly impact the efficiency of face milling high-hardness steels. The presented analytical research results can be valuable for engineers and technologists involved in the development and improvement of machining processes for hard materials to further enhance surface roughness in face milling.